A Politically Commercial Media System - Guðmundsson, Birgir (Veftímaritið Stjórnmál og stjórnsýsla, 2013)
"The third Age of Political Communication" and includes e.g. increased communication expertise within the political parties as well as professionalization of journalism, thus has had shorter time to develop than in many of the neighbouring countries. In this article the results of a survey among candidates from all political parties and all constituencies in the 2013 parliamentary elections are reported. The findings categorically show that politicians have little faith in the professionalization, impartiality and balance to political parties of the Icelandic media and journalists, characteristics that would be expected to follow the commercialisation of the Media System and transformation from external diversity to internal diversity (Hallin and Mancini, 2004). Icelandic politicians on the contrary view the Media in a political light where political parallelism and external diversity is important. It is argued that in Iceland there has developed a "Politically Commercial Media System" due to a combination of reasons. Among them are the historical proximity of a system of political parallelism, a relatively recent professionalization of journalism, an unregulated media environment and an extreme ownership concentration of the media, where ownership powers and political parties became mixed with each other. Flokksfjölmiðlun þreifst hér á landi fram undir síðustu aldamót og sú umbreyting sem Blumler and Kavanagh (1999) kölluðu "Þriðja skeið pólitískrar boðmiðlunar" og felst m.a. í aukinni sérfræðiþekkingu í boðmiðlun innan stjórnmálaflokka og mikilli fagvæðingu blaðamannastéttarinnar og fjölmiðla, hefur haft styttri tíma til að þroskast en raunin var víða í nágrannalöndunum. Í þessari grein eru birtar niðurstöður úr frambjóðendakönnun sem gerð var meðal frambjóðenda allra stjórnmálaflokka í öllum kjördæmum fyrir Alþingiskosningarnar 2013. Niðurstöðurnar sýna með afgerandi hætti að íslenskir stjórnmálamenn hafa litla tiltrú á fagmennsku blaðamanna, óhæði fjölmiðla gagnvart stjórnmálaflokkum og þeirri óhlutdrægni ...